Contrast-enhanced ultrasound in detecting wall invasion and differentiating bland from tumor thrombus during robot-assisted inferior vena cava thrombectomy for renal cell carcinoma - Li, Qiu-Yang (Cancer Imaging, 2019)
BACKGROUND: Vena cava thrombus is one of the main clinical manifestations of locally aggressive renal cell carcinoma (RCC). Inferior vena cava (IVC) wall invasion and presence of bland thrombus could affect the surgical outcome. This study aims to assess the value of contrast-enhanced ultrasound (CEUS) in detecting wall invasion and differentiating bland thrombus from tumor thrombus during robot-assisted IVC thrombectomy for RCC. METHODS: The intraoperative CEUS findings of 60 patients with RCC accompanied by IVC tumor thrombus were retrospectively analyzed. The CEUS features were compared with the intra- and post-operative pathological findings. CEUS in patients with wall invasion showed that the tumor thrombus was enhanced synchronously with the IVC wall, and the continuity of the IVC wall was lost. In contrast, in patients without wall invasion, CEUS showed that the contrast agent could pass between the tumor thrombus and the IVC wall, and the continuity of IVC wall was good. Typically, contrast-enhanced perfusion was seen in tumor thrombus but not in bland thrombus. The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of CEUS were statistically analyzed. RESULTS: The sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of the typical enhancement mode of CEUS were 93.1, 93.5, 93.3, 93.1, and 93.5% in identifying wall invasion and 100, 96, 96.7, 83.3, and 100% in differentiating bland thrombus from tumor thrombus, respectively. There were excellent inter-observer agreements for identifying IVC wall invasion and differentiating bland thrombus from tumor thrombus with kappa coefficients of 0.90 and 0.97. CONCLUSIONS: The present study indicates that intraoperative CEUS plays an important role in robot-assisted IVC thrombectomy for RCC. It can detect wall invasion and differentiate bland thrombus from tumor thrombus, thus offering real-time information to the operator during surgery.